The influence of Somatic Auditory Visualization Intellectualy (SAVI) Learning Method to Learning Outcome of Senior High School at Labuhanbatu District (in case on the Ecosystem Discussion) || Pengaruh Model Pembelajaran Somatic Auditory Visualization Intellectualy (SAVI) Terhadap Hasil Belajar Siswa SMA di Kabupaten Labuhanbatu (dikaji pada Materi Ekosistem) - Samini Samini (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2021)
This study aims to determine the effect of biology student learning outcomes in the subject matter characteristics of living creatures that learned by using SAVI learning method in the seventh grade students of SMPN I Panai Tengah Labuhanbatu district in learning year 2019/2020. This type of research is a quasi experimental study. The research sample consisted of two classes chosen at random cluster sampling the experimental class and control class. Total students each sample were 40 people in the control group and 40 in the experimental class. To obtain the data used in this study researchers used the test as a means of collecting data as much as 40 multiple choice questions. From the calculation of normality test the experimental class using learning Metode "SAVI" there is value Sig. 0,200 > 0,05 then the population of normal distribution. Homogeneity test results biology student learning using Fisher test. Retrieved 0,226 > 0,05 then have a homogeneous variance. Hypothesis testing using t test, the test requirement is received H0 tcount <ttable, and thank Ha if the conditions are not met. 0,000 < 0,05 Ha accepted hypothesis H0 is rejected. It can be concluded that there is a significant impact on learning outcomes of students that learned by Somatic Auditory Visualization Intellectualy (SAVI) methodPenelitian ini bertujuan untuk mengetahui pengaruh hasil belajar biologi siswa pada materi ekosistem yang dibelajarkan dengan menggunakan metode pembelajaran (SAVI) pada siswa kelas X SMA Negeri I Panai Tengah tahun pelajaran 2019/2020. Jenis penelitian ini merupakan penelitian quasi eksperimen. Sampel penelitian terdiri dari dua kelas yang dipilih secara cluster random sampling yakni kelas eksperimen dan kelas kontrol. Jumlah siswa masing-masing sampel adalah 40 orang pada kelas kontrol dan 40 orang pada kelas eksperimen. Untuk memperoleh data yang dipergunakan dalam penelitian ini peneliti menggunakan tes sebagai alat pengumpul data sebanyak 40 soal pilihan berganda. Dari hasil perhitungan uji normalitas pada kelas eksperimen menggunakan Metode pembelajaran SAVI terdapat Sig. 0,200 > 0,05, maka  populasi berdistribusi normal. Uji homogenitas hasil belajar biologi siswa menggunakan uji statistic SPSS Diperoleh 0,226 > 0,05 maka memiliki varians yang homogen. Hasil Uji t menunjukkan nilai 0,000 < 0,05. Hal ini berarti bahwa taraf signifikan α = 0,05 H0 ditolak Ha diterima. Sehingga dapat disimpulkan bahwa terdapat pengaruh yang signifikan terhadap hasil belajar biologi siswa yang dibelajarkan dengan Metode pembelajaran Somatic Auditory Visualization Intellectualy (SAVI)